(3GdehLR aj efgL GdHMK GdYdej aj GdJQHjI hGdYdhe GdEfSGfjIs - (3YeQ, Sja GdESdGe SYOs ((3HjQhJs (3OGQ GdacQ GdeYGUQs, 2009)
(3jJfGhd efgL GdHMK GdYdej Heagheg hNUGFUg hGdHMK GdJQHhj hWHjYJg heTcdGJg hCNdGbjGJg hcjajI EYOGO eNWW GdHMK hhSGFd LeY GdeGOI GdYdejI hCfhGY efGgL GdHMK GdYdej hhSGFdg hCOhGJg hYjfGJ GdHMK hCSdhH JMdjd GdeMJhi hUjGZI hJhKjb JbQjQ GdHMK eY eQGLY eNJGQI aj efGgL GdHMK(B. (3bSe GdeDda cJGHg Edi KeGfjI aUhd; GdChd JfGhd efgL GdHMK GdYdej ef MjK Gdeaghe, eaUdkG HGdJYQja, ehVMkG BQGA GdYdeGA aj GdJacjQ GdYdej, eJfGhdkG OhQ GdMGShH aj NOeI GdHMK(B. (3hNUU GdaUd GdKGfj ddMOjK Yf GdHMK GdJQHhj aj eagheg hWHjYJg heTcdGJg hCNdGbjGJg hGdCNWGA GdcGefI ajg(B. (3hJMOK aj GdaUd GdKGdK Yf EYOGO eNWW GdHMK hYfGUQg hGdJUeje GdefgLj ddHMK(B. (3hHnqjf aj GdaUd GdQGHY hSGFd GdMUhd Ydi GdeGOI GdYdejI hGdWQGFb GdeajOI aj Pdc, hTQM aj CKfGA Pdc YOOkG ef GdWQGFb cGdbQGAI hGdJOhjf hGdGbJHGS hGdedGMXI hGdJLQHI(B. (3hYQV aj GdaUd GdNGeS CfhGY GdHMhK hGdeYGjjQ GdJj JUfa Ydi CSGSgG GdefGgL GdHMKjI, hCTGQ Edi GdHMK GdhUaj hGdHMK GdJGQjNj hGdHMK GdJLQjHj(B. (3hTQM aj GdaUd GdSGOS COhGJ GdHMK GdYdej GdJj JNJda ef Yed Edi BNQ; ef CLgRI GdbjGS Edi COhGJ GdaMU Edi ELQGA GdGNJHGQ Edi GSJeGQGJ GdGSJaJGA hZjQ Pdc(B. (3hYGdL aj GdaUd GdSGHY eaghe GdYjfI hGdeLJeY, hGdWQGFb aj GNJjGQ GdYjfGJ, hJbOjQ GdMLe GdefGSH ddYjfI hCKQg aj eOi GdKbI HfJGFL GdHMK(B. (3hhba aj GdaUd GdKGef GdCNjQ YfO CSdhH JMdjd GdeMJhi aj fTCJg heagheg, Ke cjajI cJGHI JbQjQ GdHMK hNUhUkG ajeG jJYdb HYQV GdfJGFL hJaSjQgG hcJGHI GdJhUjGJ hGdebJQMGJ, hcJGHI GdeQGLY hGdJhKjb hGSJNOGe GdMhGTj(B.s
(3GdfhY (B: (3cJGHs
Keywords: Educational Research; Recherche en Education; (3GdHMK GdJQHhjs